Survey On Prevalence And Pharmacological Approaches In Non-Alcoholic Fatty Liver Disease And Steatohepatitis - N Lalaji, Aniket; J Paul, Sattwik; Pineshbhai, Patel Dhruvi; Sharma, Ujjawal; Jamsa, Anas (Journal of Neonatal Surgery, 2025)
Introduction: Non-Alcoholic Fatty Liver Disease and Non-Alcoholic Steatohepatitis have emerged as significant public health concerns, closely linked to metabolic syndrome. This study aimed to assess the prevalence, associated risk factors, and pharmacological approaches for managing NAFLD/NASH. Material And Methods: A cross-sectional study was conducted on 191 adult patients diagnosed with NAFLD or NASH based on clinical assessments, laboratory parameters, and imaging findings. Data on demographics, comorbidities, pharmacological treatments, and biochemical markers were analyzed to evaluate disease severity and treatment patterns. Results: NAFLD was most prevalent among middle-aged adults (40–50 years), with a male predominance. Obesity (46.07%) and overweight status (30.36%) were the most common risk factors. Fibroscan findings indicated that 49.73% of patients had moderate fibrosis, while 17.80% had severe fibrosis. Elevated aspartate aminotransferase(AST),alanine aminotransferase( ALT), and ferritin levels were significantly associated with fibrosis severity. Pharmacological management predominantly involved vitamin E (46.07%), atorvastatin (43.97%), metformin (25.65%), and GLP-1 receptor agonists (29.84%), reflecting a growing focus on metabolic modulation in NAFLD treatment. Conclusion: The study reinforces the strong association between NAFLD and metabolic dysfunction. While no FDA-approved treatment exists, the current therapeutic landscape relies on insulin sensitizers, lipid-lowering agents, and antioxidants. Early diagnosis and intervention through metabolic control remain crucial in mitigating disease progression. Further research is warranted to establish standardized treatment guidelines and assess long-term outcomes of pharmacological interventions.